Proceedings of SYSTOR 2009: The Israeli Experimental Systems Conference 2009
DOI: 10.1145/1534530.1534536
|View full text |Cite
|
Sign up to set email alerts
|

Energy and performance evaluation of lossless file data compression on server systems

Abstract: of the Thesis Energy and Performance Evaluation of Lossless File Data Compression on Computer Systems by Rachita Kothiyal Master of Science in Computer ScienceStony Brook University 2009Data compression has been claimed to be an attractive solution to save energy consumption in high-end servers and data centers. However, there has not been a study to explore this. In this thesis, we present a comprehensive evaluation of energy consumption for various file compression techniques implemented in software. We appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Some of our own past studies show significant energy savings possible in commodity Linux servers running common workloads such as Web, email, database, compression, etc. [23,33]. Generally, optimal use of energy-saving techniques requires accurate models of system energy consumption with respect to appropriate parameters; the work described in this paper is a step towards the development of such models.…”
Section: Energy Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Some of our own past studies show significant energy savings possible in commodity Linux servers running common workloads such as Web, email, database, compression, etc. [23,33]. Generally, optimal use of energy-saving techniques requires accurate models of system energy consumption with respect to appropriate parameters; the work described in this paper is a step towards the development of such models.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…Our prior work, conducted by Kothiyal et al, evaluated energy consumption and performance of data compression on servers [23] and demonstrated that compression reduces energy consumption in some situations but not all. A careful application of compression can save energy in some cases by a factor of 10×, but a careless application of compression can easily waste energy and slow performance by 200×.…”
Section: Energy Consumption Of Data Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…GreenFS is a stackable file system that combines a remote network disk and a local flash-based memory buffer to keep the local disk idling for as long as possible [20]. Kothiyal et al examined file compression to improve power and performance [23].…”
Section: File System Studiesmentioning
confidence: 99%
“…This is because affordable storage continues to be orders of magnitude slower than any other component, such as the CPU, RAM, or even a fast local network. Any software that uses storage heavily, such as major scientific applications, transactional systems [40,64], databases [45], file systems [31,57,58,61,65], and more, are designed around the large difference in performance between RAM and storage devices. Using a flexible cluster architecture that can scale well with an increasing number of nodes is an excellent way to prorate these storage and computing costs [14].…”
Section: Introductionmentioning
confidence: 99%